Analisis Penerimaan dan Pengeluaran Barang Umum Non Curah Pada Gudang Perbekalan PT. Semen Padang - Amanda Febria Sari (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2011)
Inventory has its advantages and disadvantages. The advantage of this inventory is to beable to anticipate the urgent needs of the company, meet the demand from users. But thisstock has a loss, which can increase the costs to be incurred by the company so as to reducethe advantage held by the company. The more the amount of inventory in warehouse, themore the cost of inventory that must be removed and inventory turnover (ITO) whichproduced the lower. One way to do inventory control is to determine the optimal orderquantity. The method used to determine the optimal number of reservations is to use theEOQ method by considering the amount of safety stock and reorder point when done. Basedon the calculations have been performed for the optimal order quantity are 2,019 bottles ofoxygen, welding wirerod is 14,795 stems, and 185 stem of pipe metal. By doing of EOQ toinventory control obtained by the method of ITO increases the weld wire and pipe metalfrom 0.0392 to 1.1010 at the welding wire and from 0.2949 to 0.8627 on a pipe metal.However, the oxygen has decreased from 1.9238 to 1.6094 so that it can be concluded thatthe EOQ method can not be applied to the oxygen, but can be applied to the weldingwire and pipe metal.